Application of Value Chain Strategy to Ensure the Sustainability of Online Transportation Services - Rini Mulyani Sari; Evan Nugraha; Asep Kurniawan (Politeknik APP Jakarta, 2025)
Technological advancements have greatly impacted various aspects of modern life, including the transportation industry. The aim of this research is to enhance organizational efficiency by implementing lean supply chain principles to online transportation services in Indonesia. This study employed an exploratory analytical qualitative approach to analyze the research variables. The methodology used involved distributing questionnaires and conducting interviews with 120 users of online transportation services. The novelty of this research is to examine the application of the value chain in the service industry, specifically in online transportation service. The study concludes that online transportation service apps should increase traceability to ensure that the driver closest to the client receives the order, implementing a user-friendly feature, enhance the application’s performance, and increase the response time.